Reproducibility of Retinal Nerve Fiber Layer and Macular Thickness Measurement by Spectral Domain Optical Coherence Tomography - A. K. Sood; R. O. Paliwal; R. Y. Mishra (Oftalʹmologiâ)
Purpose: To assess the reproducibility of retinal nerve fiber layer (RNFL) and macular thickness by spectral domain optical coherence tomography (SD-OCT) when the same investigator does scan thrice in a span of one hour without reference to the previous scan, is able to get similar results or not, without using the repeat function.Methods. In this prospective observational study 200 subjects who fulfilled the inclusion & exclusion criteria were scanned 3 times as per pre-defined guidelines at 0 minutes, 30 minutes; 60 minutes on the same day, by the same investigator using SD-OCT for measurements of RNFL and macular thickness & observations were statistically analyzed & correlated.Results. In RNFL thickness, temporal sector shows the worst reproducibility as compared to other sectors. The RNFL thickness was greatest in superior quadrant and thinnest in temporal quadrant. Female values were significantly higher than males in RNFL superior and RNFL symmetry. For macular thickness, temporal sector (mid-zone) showed the worst reproducibility and in outer-zone, Inferior sector showed the worst reproducibility. It also shows that macular thickness was thinnest at the central zone (innermost 1 mm ring), thickest within the inner 3 mm ring and diminished peripherally.Conclusion. RNFL and macular thickness measurements by SD-OCT by the same observer at 0 minutes, 30 minutes and 60 minutes were very reproducible except in the sectors specifically mentioned. The greater the thickness of RNFL in any sector, the better will be the reproducibility in that sector. For macular thickness, temporal sector (mid-zone) showed the worst reproducibility & with an increase in age the macular thickness measurements decreases.